(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Upper gastrointestinal bleeding is an acute emergency condition. It is an important cause for the hospital admission. This study descriptively analyses the clinical profile of upper gastrointestinal bleeding presenting to a tertiary hospital in Nepal. Method: This is a cross-sectional study of patients presenting with upper gastrointestinal bleeding from 01 Oct 2018 to 30 Sep 2019 at Patan Hospital Emergency Department, Patan Academy of Health Sciences, Nepal. Patient’s demographics, clinical presentation, duration of illness before presenting to Emergency, vitals, and laboratory parameters were descriptively analyzed. Ethical approval was obtained. Result: There were 121 patients, male 82(67.8%) and female 38(31.4%) aging 14 to 90 years. Fifty-three patients (43.8 %) presented with hematemesis, 38(31.4%) with melena, and 27(22.3%) with both hematemesis and melena. Variceal bleeding was the main cause of upper gastrointestinal bleeding found in 73(60.33%) followed by ulcer bleeding in 48(39.66%). Conclusion: Variceal bleeding was the main cause of upper gastrointestinal bleeding and hematemesis was the most common clinical presentation in patients presenting to the Emergency Department.